IMPLEMENTATION OF ANALYTICAL HIERARCHY PROCESS & BEST WORST METHOD IN SUPPLIER SELECTION - Nanang Alamsyah; Mohammad Rachman Waluyo; Muthia Zenzy Ariani (UIN Sumatera Utara, 2022)
The incompatibility of the quality of the goods sent and the delay in delivery resulted in the company suffering losses and creating an unfavourable image in the company consumer's eyes. Both factors can be caused by error in the supplier selection process of raw material. The purpose of this research is to select the best supplier in the procurement process at the largest paper-producing company in Indonesia, which begins with determining the criteria that influence the selection of suppliers. The Analytical Hierarchy Process and the Best Worst Method were used in this study. Based on 4 personnel in the procurement department, 8 criteria were found for selecting suppliers with 3 alternative suppliers. The selected criteria are: Certificate Quality, Defect Rate, Offer Price, Discounts, Delivery Time, Order Fulfilment, Power Respond, and Work History. The offer price is the most important variable with a weight of 29.3%. Supplier A was selected with a score of 66.78%, while Supplier C became the second alternative priority and Supplier B became the third alternative priority.